Gestalt therapy : history, theory, and practice - Woldt, Ansel L.; Toman, Sarah M. (Sage Publications, 2005)
Gestalt Therapy: History, Theory, and Practice is an introductory text, written by major Gestalt theorists, that will engage those new to Gestalt therapy. Editors Ansel Woldt and Sarah M. Toman introduce the historical underpinnings and fundamental concepts of Gestalt therapy and illustrate applications of those concepts to therapeutic practice. The book is unique in that it is the first Gestalt text specifically designed for the academic and training institute settings. Gestalt Therapy takes both a conceptual and a practical approach to examining classic and cutting-edge constructs.